Interaction Between HIV-1 Nef and Calnexin: From Modeling to Small Molecule Inhibitors Reversing HIV-Induced Lipid Accumulation. Issue 9 (September 2016) - Hunegnaw, Ruth; Vassylyeva, Marina; Dubrovsky, Larisa; Pushkarsky, Tatiana; Sviridov, Dmitri; Anashkina, Anastasia A.; Üren, Aykut; Brichacek, Beda; Vassylyev, Dmitry G.; Adzhubei, Alexei A.; Bukrinsky, Michael
Abstract : Objective—: HIV-infected patients are at an increased risk of developing atherosclerosis, in part because of downmodulation and functional impairment of ATP-binding cassette A1 (ABCA1) cholesterol transporter by the HIV-1 protein Nef. The mechanism of this effect involves Nef interacting with an ER chaperone calnexin and disrupting calnexin binding to ABCA1, leading to ABCA1 retention in ER, its degradation and resulting suppression of cholesterol efflux. However, molecular details of Nef–calnexin interaction remained unknown, limiting the translational impact of this finding. Approach and Results—: Here, we used molecular modeling and mutagenesis to characterize Nef–calnexin interaction and to identify small molecule compounds that could block it. We demonstrated that the interaction between Nef and calnexin is direct and can be reconstituted using recombinant proteins in vitro with a binding affinity of 89.1 nmol/L measured by surface plasmon resonance. The cytoplasmic tail of calnexin is essential and sufficient for interaction with Nef, and binds Nef with an affinity of 9.4 nmol/L. Replacing lysine residues in positions 4 and 7 of Nef with alanines abrogates Nef–calnexin interaction, prevents ABCA1 downregulation by Nef, and preserves cholesterol efflux from HIV-infected cells. Through virtual screening of the National Cancer Institute library of compounds, we identified a compound, 1[(7-oxo-7H-benz[de]anthracene-3-yl)amino]anthraquinone, which blocked Nef–calnexin interaction, partially restored ABCA1 activity in HIV-infected cells, and reduced foam cell formation in a culture of HIV-infected macrophages. Conclusion—: This study identifies potential targets that can be exploited to block the pathogenic effect of HIV infection on cholesterol metabolism and prevent atherosclerosis in HIV-infected subjects. Abstract : Supplemental Digital Content is available in the text.